1981
DOI: 10.1524/anly.1981.1.2.149
|View full text |Cite
|
Sign up to set email alerts
|

On the Mean Value of L(1/2, χ ) FW Real Characters

Abstract: Asymptotic formulae are derived for the sums ZL''(i,x), where k=l or 2 and x runs over all Dirichlet characters defined by Kronecker's symbol ^ with d being restricted to fundamental discriminants in the interval [-A'.O) or (0,jr]. Also, asymptotic formulae are proved for the sums where Zp('')=(") is defined by the Legendre symbol and p is restricted to primes p^X with/) = i; (mod 4),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 7 publications
7
134
0
Order By: Relevance
“…Jutila [11], verifying a conjecture of Goldfeld and Viola [10], showed that (1.1) 0<±d<X L(1/2, χ d ) ∼ c 1 X log X + c 2 x + O(x 3/4+ ) for certain constants c 1 , c 2 . Takhtadzjan and Vinogradov [15] establish a similar result.…”
Section: Introductionmentioning
confidence: 60%
“…Jutila [11], verifying a conjecture of Goldfeld and Viola [10], showed that (1.1) 0<±d<X L(1/2, χ d ) ∼ c 1 X log X + c 2 x + O(x 3/4+ ) for certain constants c 1 , c 2 . Takhtadzjan and Vinogradov [15] establish a similar result.…”
Section: Introductionmentioning
confidence: 60%
“…Having the generating function, Msp(N, 8), it is a short step to find the value distributions of both log Z(U, 0) and…”
Section: {22}mentioning
confidence: 99%
“…(47) is the success of a very similar conjecture relating moments of the Riemann zeta function to averages over U(N) [7]. The only difference is that in the case of (8) the average was along the critical line rather than over a family of functions. This is not a significant difference, however, and Conrey and Farmer in fact suggest that we think of the Riemann zeta function as a unitary family (with zeros showing the statistics of the eigenvalues of matrices from U(N» in its own right, where we are averaging over special values of the family {(1/2 +it)} as t ranges over the real numbers.…”
Section: L-functions With Symplectic Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…But we can also consider the problem of averaging over fundamental discriminants. In 1979, Goldfeld and Viola [10] put forward a few conjectures about averages over fundamental discriminants and Jutila [13] proved such conjecture in 1981 for s = 1 2 . Then, in 1985, Goldfeld and Hoffstein [9], using Eisentein series of 1 2 -integral weight, generalized Jutila's result and proved a result valid for all s with Re(s) ≥ 1 2 .…”
Section: Conjecture 11 (Gauss) Let H D Be the Class Number Defined Amentioning
confidence: 99%